2020
DOI: 10.3390/jcm9124014
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Surgery for Graves’ Disease in Germany

Abstract: Background: Surgical treatment of Graves’ disease (GD) has a potentially increased incidence of postoperative hypoparathyroidism, recurrent laryngeal nerve palsy (RLNP) and bleeding. The aim of this study was to evaluate the current extent of surgery for the treatment of GD and its safety as a short-term outcome. Methods: Patients who underwent thyroid resection for GD were identified from the prospective StuDoQ/Thyroid registry. Patient data were retrospectively analyzed regarding demographics, surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Intraoperative nerve monitoring (IONM) was used in 98.9% of the cases. The rate of unilateral transient RLN injury was 3.9%, 57 compared with a 2.74% rate found on a meta‐analysis for IONM in thyroid surgeries 66 . This comparable rate may stress the importance of IONM in GD patients.…”
Section: Possible Clinical Concerns Regarding Surgical Management Of Gdmentioning
confidence: 73%
See 4 more Smart Citations
“…Intraoperative nerve monitoring (IONM) was used in 98.9% of the cases. The rate of unilateral transient RLN injury was 3.9%, 57 compared with a 2.74% rate found on a meta‐analysis for IONM in thyroid surgeries 66 . This comparable rate may stress the importance of IONM in GD patients.…”
Section: Possible Clinical Concerns Regarding Surgical Management Of Gdmentioning
confidence: 73%
“…Numerous studies, from both Europe and the United States, have found that high‐volume thyroid centres have a lower complication rate, yet the cutoff for high‐volume ranged from 25 to 50 surgeries per year 57,67 . The authors agree that GD patients should only be treated in dedicated centres that have a high‐volume endocrine practice.…”
Section: Possible Clinical Concerns Regarding Surgical Management Of Gdmentioning
confidence: 97%
See 3 more Smart Citations